Enhancing self-care ability among older persons in a community home-based setting - San Juan, Mila Grace C. (Manila University of the Philippines Open University Learning Center, 2012)
This study was conducted to determine the effects of the OBIESCA intervention in enhancing the self-care ability among older persons in a community home-based setting in Davao City. Particularly, this study was conducted (1) To determine the level of self-care ability of older persons in community homes (2) To determine if there is a significant difference in the level of self-care ability of older persons in community homes before and after the intervention (3) To determine if there is a significant difference in the level of self-care ability of older persons between the study group and comparison group (4) To describe what are the experiences of nurses in the implementation of OBIESCA. -- The post-assessment on study group and comparison group was used. The OBIESCA intervention was tested on older persons at the Care for the Elderly Foundations, Inc. Nurses together with caregivers followed the intervention protocol based on the concept of self-care theory of Dorothea Orem with nursing system, specifically in the aspects of fully compensatory, partly compensatory, and supportive educative nursing role. The Instrumental Activities of Daily Living (IADL) from Lawton M.P., Brody E.M. and evaluation form for Katz Index of ADL was used. It was utilized as pre-assessment and post-assessment tool of level of self-care ability of older persons in the study group and comparison group. The nurse made used of the personal data sheet for the socio demographic profile of older persons. -- A total of 87 older persons (43 in the study group and 44 in the comparison group) participated in the study. Majority of the clients in both groups were single and widowed. More than half (23, 53.5%) of the clients in the experimental group and thirteen (13, 29.5%) of the clients assigned in the comparison group reached a college level of education. Majority of the older persons (39.5 % and 63.6 %) are in the age group of 60-74 both in the study group and comparison group, respectively. As to their income status, it shows that most of the study group belongs to both low and middle income while majority of the comparison group belongs to low income. -- The findings of the study showed that there was no significant difference between two group noted in terms of the following variables: age (χ² = 5.44, p= 0.07), length of stay (t = 1.26, p= 0.21), (χ² = 7.29, p= 0.41) and income (χ²= 3.70, p= 0.16) except for civil status (χ²= 9.03, p= 0.02). There was a significant difference between pre-test and post-test after the intervention on the following variables: food preparation (p= 0.00), housekeeping (p= 0.00) and dressing (p= 0.00). There was no significant difference between pre-test and post-test in the comparison group in all IADL and KATZ index variables (p>0.05). -- Orem Based-Intervention for older persons in the community was effective in enhancing self-care ability specifically food preparation, housekeeping and dressing. The results generated important implications to nursing practice and research. Training/lecture discussion on Orem-Based Intervention for Enhancing Self-Care Ability of Older Persons (OBIESCA) for staff nurses and caregivers should be included in nursing homes. This may be more effective if this will be followed by the use of OBIESCA nurse training program. The categorization of self-care ability of older persons to cater the appropriate care they need. The use of the Instrumental Activities of Daily Living (IADL) from Lawton M.P., Brody E.M., and evaluation form from Katz Index of ADL should be used to assess the self-care ability of older persons before and after the intervention.
Thesis (Master of Arts in Nursing - Major in Adult Health Nursing) -- University of the Philippines Open University Learning Center, March 2012.
Bibliography: 76-89 leaves.
Keywords: Older people -- Self-care, Health